SMART-R Counseling: Developing Student Resilience during the COVID-19 Pandemic - Suranata, Kadek; Paramartha, Wayan Eka; Dharsana, I Ketut; Abu Bakar, Abu Yazid (Department of Guidance and Counseling, FIP, Undiksha, 2022)
The COVID-19 pandemic that has lasted for two years is a dynamic condition that has an impact on all dimensions of life, including educational field. Various changes that appear in learning activities at school can not be denied has become a stressful situation that requires students to adapt quickly. Several findings have shown that there is a decrease in students' psychological well-being during the pandemic. This condition emphasizes that students need to have good psychological resilience so they are able to face difficulties and misfortunes, and be adaptive due the changes. The development of student resilience can be done through guidance and counseling services. SMART-R is a strength-based counseling model that can be implemented by counselors (BK teachers) to develop student resilience. Through the implementation of SMART-R counseling, students can have a more adaptive response in dealing with pressures and changes due to the COVID-19 pandemic, and can develop more positive feelings, thoughts, and behaviors.